2023
DOI: 10.3390/w15050921
|View full text |Cite
|
Sign up to set email alerts
|

Microplastic Toxicity and Trophic Transfer in Freshwater Organisms: Ecotoxicological and Genotoxic Assessment in Spirodela polyrhiza (L.) Schleid. and Echinogammarus veneris (Heller, 1865) Treated with Polyethylene Microparticles

Abstract: The widespread occurrence of microplastics (MPs) has resulted in their interaction with biological processes. Thus, there is a great concern about the potential toxicity of MPs on animal and plant cells and on the possibility that MPs reach humans through the food web. In order to shed light on both issues, laboratory assays were performed for evaluating the effects of polyethylene (PE) microparticles on the aquatic plant Spirodela polyrhiza (L.) Schleid. and the gammarid Echinogammarus veneris (Heller, 1865).… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2
1

Citation Types

0
4
0

Year Published

2023
2023
2024
2024

Publication Types

Select...
6

Relationship

2
4

Authors

Journals

citations
Cited by 6 publications
(7 citation statements)
references
References 80 publications
0
4
0
Order By: Relevance
“…Furthermore, Hyalella azteca individuals were found to ingest MPs during 10-day exposures to PE particles (10-27 µm in diameter) and PP fibres (20 µm-75 µm in length and 20 µm in diameter). Recent research by Iannilli et al [8] demonstrated the ingestion of MPs by Echinogammarus veneris in laboratory conditions when the organisms were exposed to Spirodela polyrhiza plants contaminated with PE microparticles measuring approximately 50 µm.…”
Section: Resultsmentioning
confidence: 99%
See 2 more Smart Citations
“…Furthermore, Hyalella azteca individuals were found to ingest MPs during 10-day exposures to PE particles (10-27 µm in diameter) and PP fibres (20 µm-75 µm in length and 20 µm in diameter). Recent research by Iannilli et al [8] demonstrated the ingestion of MPs by Echinogammarus veneris in laboratory conditions when the organisms were exposed to Spirodela polyrhiza plants contaminated with PE microparticles measuring approximately 50 µm.…”
Section: Resultsmentioning
confidence: 99%
“…MPs may contain toxic compounds that can disrupt the amphipods' endocrine system [50], affecting hormone production and altering energy metabolism, leading to a reduction in energy reserves. Additionally, the presence of MPs in the gastrointestinal tract can cause physical and physiological stress, resulting in irritation, inflammation [8], and the need for increased energy expenditure to repair damaged tissues. Environmental stress caused by the presence of MPs can have a significant impact on an organism's energy balance, as it requires additional energy to recover and maintain homeostasis.…”
Section: Resultsmentioning
confidence: 99%
See 1 more Smart Citation
“…This characteristic, and their trophic role (primary consumers, detritivores, and polyphages) in aquatic environments, make them particularly suitable as bioindicators in toxicity tests [55]. MPs ingestion was documented in several marine species [56][57][58], and studies tested the MPs toxicity and genotoxicity on them at a lab scale [59][60][61][62].…”
Section: The Need For Bioindicatorsmentioning
confidence: 99%
“…These organisms ingest this microplastic debris while ingesting their food as well [18]. There have been many studies on the ingestion of microplastics by freshwater organisms, both vertebrates and invertebrates, with fish being the most studied group of aquatic organisms [19] and followed by other freshwater organisms, such as zooplankton (Daphnia magna) [20], arthropods (Chironomus riparius), gastropods (Physella acuta), annelids (Lumbricus variegatus) [21], crustaceans (Echinogammarus veneris) [22], diatoms (Cyclotella meneghiniana) [23], etc. However, sponges (Porifera) themselves are still very poorly studied in microplastic research [24], especially in Indonesia.…”
Section: Introductionmentioning
confidence: 99%